The Relationship Between Job Type and the Incidence of Osteoarthritis at the Unaaha Community Health Center - Miranda Septiani; Amirudin Eso; La Rangki (Jurnal Sehat Indonesia (JUSINDO), 2026)
Osteoarthritis (OA) is a degenerative joint disease characterized by damage to joint cartilage. Osteoarthritis can be influenced by several factors, namely systemic factors (age, sex, and heredity), intrinsic factors (anatomical abnormalities and injuries), and extrinsic factors (obesity, joint overuse, and occupation). This study aims to determine the relationship between job type and the incidence of osteoarthritis at the Unaaha Community Health Center. This study uses an analytical observational method with a cross-sectional approach. This research was conducted in the Konawe Regency area, specifically at the Unaaha Community Health Center. The sample in the study consisted of 68 respondents obtained using the purposive sampling technique. Data were obtained through medical records and then analyzed using the chi-square test and were considered statistically significant if p < 0.05. The results of the bivariate analysis examining the relationship between job type and the incidence of osteoarthritis at the Unaaha Community Health Center yielded a value of p = 0.034, which is less than α (0.05); thus, it can be stated that there is a statistically significant relationship between job type and the incidence of osteoarthritis. The conclusion of this study is that there is a significant relationship between job type and the incidence of osteoarthritis at the Unaaha Community Health Center.